Application of Biosecurity Strategies for the Control of MAS (Motile Aeromonas Septicemia) in Tubifex Worms (Tubifex sp.) for Larval Catfish (Pangasius sp.) Culture - Firdausi, Amalia Putri; Indriastuti, Cecilia Eny; Surahman, Nur Prasetyo Ari; Permatasari, Sheny (Research and Social Study Institute, 2025)
Background: Catfish (Pangasius sp.) is one of the high-value freshwater aquaculture commodities in Indonesia. To ensure sustainable production, hatchery management plays a crucial role, as the larval and juvenile stages are the most vulnerable to environmental stress and disease outbreaks. During the larval phase (7–14 days post-hatch), Tubifex worms (Tubifex sp.) are commonly used as a natural feed due to their high nutritional content and digestibility.Aims & Methods: This study aimed to evaluate the effectiveness of formalin in suppressing Aeromonas hydrophila in Tubifex worms (Tubifex sp.), which are used as natural feed for larval catfish (Pangasius sp.). The research was conducted in two phases: in vitro and in vivo assays. The in vitro assay was carried out to determine the minimum inhibitory concentration (MIC) and inhibition zone of formalin against A. hydrophila. The in vivo assay consisted of two parts: a toxicity test of formalin on Tubifex worms and an evaluation of the effect of treated worms as feed on the survival of catfish larvae. A completely randomized design (RAL) was employed, consisting of four treatments with three replicates each: K (control—untreated Tubifex), A (400 ppm formalin immersion without rinsing), B (400 ppm formalin immersion with one rinse), and C (400 ppm formalin immersion with two rinses).Result: The results demonstrated that a 400 ppm formalin concentration effectively inhibited the growth of A. hydrophila. Treatment C (two rinses following immersion in 400 ppm formalin) significantly reduced the toxic effects of formalin on the Tubifex worms used as natural feed. Consequently, this treatment led to an improvement in the survival rate of catfish larvae, reaching 44.6 ± 11.5% over a 14-day rearing period.